IMPLEMENTASI MEDIA PEMBELAJARAN HIDROKARBON BERORIENTASI CHEMISTRY TRIANGLE DI SMA NEGERI KOTA PADANG - Ira Mahartika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This research investigate the effect of media hydrocarbon Chemistry Triangle oriented on the high, medium, and low level school in Padang and to identify the interaction between the school level and treatment of chemical learning. This experimental study used a randomized posttest-only control group design. The experimental group experienced a media-based hydrocarbon chemistry triangle lesson while the control group was treated by conventional approach. The student participants were divided into high, medium, and low level schools based on their group mean score on the UN chemistry subject test in the academic year 2013/2014. Posttest score data were analyzed by using a T-test and two way ANOVA. This research concluded that (1) overall, the scores of students who were treated with the Media Hydrocarbon Chemistry Triangle were higher than students receiving the conventional treatment, and (2) there is no interaction between the use of instructional media and the school level. This means that instructional media has a good effect on students outcomes.